Characteristic of sausages as influenced by partial replacement of pork back-fat using pre-emulsified soybean oil stabilized by fish proteins isolate - Cheetangdee, Nopparat (Agriculture and Natural Resources, 2017)
Substitution of animal fat with oils rich in n-3 is a feasible way to improve the nutritive value of comminuted meat product. The effect on the characteristics of sausages was investigated of partial replacement of porcine fat with soybean oil (SBO) using a pre-emulsification technique. Fish protein isolate (FPI) produced from yellow stripe trevally (Selaroides leptolepis) was used as an emulsifier to prepare pre-emulsified SBO (preSBO), and its concentration effect (1%, 2% and 3%, w/v) was observed in comparison with soy protein isolate (SPI). Substitution of porcine fat using preSBO enhanced the product stability. SPI exhibited better emulsifying ability than FPI. However, FPI was more effective at reinforcing the protein matrix of the sausages than SPI, as suggested by a lowered cooking loss and the restored textural attributes of the sausages formulated with FPI stabilized preSBO. The effective concentration of FPI to improve the product stability was 2%. This work suggested that FPI was promising in the preparation of emulsified meat products.